If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x(3x + 2) = (x + 3)(4x + -1) Reorder the terms: 2x(2 + 3x) = (x + 3)(4x + -1) (2 * 2x + 3x * 2x) = (x + 3)(4x + -1) (4x + 6x2) = (x + 3)(4x + -1) Reorder the terms: 4x + 6x2 = (3 + x)(4x + -1) Reorder the terms: 4x + 6x2 = (3 + x)(-1 + 4x) Multiply (3 + x) * (-1 + 4x) 4x + 6x2 = (3(-1 + 4x) + x(-1 + 4x)) 4x + 6x2 = ((-1 * 3 + 4x * 3) + x(-1 + 4x)) 4x + 6x2 = ((-3 + 12x) + x(-1 + 4x)) 4x + 6x2 = (-3 + 12x + (-1 * x + 4x * x)) 4x + 6x2 = (-3 + 12x + (-1x + 4x2)) Combine like terms: 12x + -1x = 11x 4x + 6x2 = (-3 + 11x + 4x2) Solving 4x + 6x2 = -3 + 11x + 4x2 Solving for variable 'x'. Reorder the terms: 3 + 4x + -11x + 6x2 + -4x2 = -3 + 11x + 4x2 + 3 + -11x + -4x2 Combine like terms: 4x + -11x = -7x 3 + -7x + 6x2 + -4x2 = -3 + 11x + 4x2 + 3 + -11x + -4x2 Combine like terms: 6x2 + -4x2 = 2x2 3 + -7x + 2x2 = -3 + 11x + 4x2 + 3 + -11x + -4x2 Reorder the terms: 3 + -7x + 2x2 = -3 + 3 + 11x + -11x + 4x2 + -4x2 Combine like terms: -3 + 3 = 0 3 + -7x + 2x2 = 0 + 11x + -11x + 4x2 + -4x2 3 + -7x + 2x2 = 11x + -11x + 4x2 + -4x2 Combine like terms: 11x + -11x = 0 3 + -7x + 2x2 = 0 + 4x2 + -4x2 3 + -7x + 2x2 = 4x2 + -4x2 Combine like terms: 4x2 + -4x2 = 0 3 + -7x + 2x2 = 0 Factor a trinomial. (1 + -2x)(3 + -1x) = 0Subproblem 1
Set the factor '(1 + -2x)' equal to zero and attempt to solve: Simplifying 1 + -2x = 0 Solving 1 + -2x = 0 Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -2x = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -2x = 0 + -1 -2x = 0 + -1 Combine like terms: 0 + -1 = -1 -2x = -1 Divide each side by '-2'. x = 0.5 Simplifying x = 0.5Subproblem 2
Set the factor '(3 + -1x)' equal to zero and attempt to solve: Simplifying 3 + -1x = 0 Solving 3 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + -1x = 0 + -3 Combine like terms: 3 + -3 = 0 0 + -1x = 0 + -3 -1x = 0 + -3 Combine like terms: 0 + -3 = -3 -1x = -3 Divide each side by '-1'. x = 3 Simplifying x = 3Solution
x = {0.5, 3}
| a-2a=(8a-8)-1 | | X+.6=.9 | | x+0.054=-1.803 | | 8x-(3x+11)=29 | | .125=.333x | | (15-d)/12=37.5/75 | | 2+8x^2+8x=9x^2 | | 6-2y-6(-3y+7)ify=3 | | 3(2/8) | | (2+3y)(4x+5y)= | | 5.285-3.5x=0 | | m/9-9=-18 | | 5.285-3.25x=0 | | y(y)+14y+13=0 | | X+.5+.25=2.75 | | 7c(5-2c^2+c^3)= | | x-(x*(20/100))=120 | | .75-x=10.45 | | 9m-3=6 | | 3(2y+4)=12y-12 | | 1.4n=2n+3.2 | | 8y=24-6x | | m=n-p/r-5 | | X+.4=.7 | | 7U=12 | | 1.4(-2)=2(-2)+3.2 | | 4a^2+52a-120=0 | | -16t(t)+8t-8=0 | | 66*6= | | 4*(3*1)=5y+66 | | 5/8n=1/4 | | 3x^2+2y^2+12x-4y+8=0 |